DESIGN PROCESS FOR THE TREATMENT OF URBAN SOLID WASTE (USW) GENERATED IN THE CONE NORTH OF LIMA CITY - Erazo Erazo, R. (2003)
In this work we present the design of a Process for the treatment of the urban salid wastes (USW) produced in the northern part of Lima. The plant will be installed in the district of Puente Piedra, region of Lima. The treatment capacily is of 1500 TM/day and ethanol, methane and diesel 2 has been produced of added value, also a higher reduction is achieved to 80% in volume of USW destination at present to the final disposition in the sanitarias fillings fields of Zapallal and The Vizcacha. The impact of the implementation ol this process will be positive so much in the technological, economic and environmental aspects.